2019
DOI: 10.1080/20008198.2019.1611091
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Stressful Experiences in Transit Questionnaire (SET-Q) and its Short Form (SET-SF)

Abstract: Background: Previous studies have demonstrated that traumatic experiences from countries of origin (so-called pre-migratory factors), as well as stressors in countries of destination (so-called post-migratory factors), are related to the extent of mental health difficulties and psychological well-being of refugees. However, numerous risks that this population is exposed to during transit have so far been neglected. Objective: The aim of this research was to construct and validate a questionnaire for assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…Barriers to care in migrants have been mainly related to help-seeking behaviors and lack of knowledge of the health care system [ 8 , 52 , 57 ]. Among mental health care providers, poor use of interpreters or lack of cultural competence are the main difficulties [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to care in migrants have been mainly related to help-seeking behaviors and lack of knowledge of the health care system [ 8 , 52 , 57 ]. Among mental health care providers, poor use of interpreters or lack of cultural competence are the main difficulties [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the special conditions of refugees, measures covering specific aspects such as particularly stressful experiences during the flight, which are not covered well by standard measures of traumatic experiences, had to be developed (e.g. the Stressful Experiences in Transit Questionnaire; Purić & Vukčević Marković, 2019). Hopefully, we soon will be able to recommend a core battery of instruments, freely available in many languagesas we have done for trauma research in general (Olff, 2015a).…”
Section: Refugeesmentioning
confidence: 99%
“…Secondly, it seems reasonable to assume that the type of interaction with people who experienced the given trauma/s more recently and which are more or less acutely distressed and affected by that experience will leave a deeper impact on the service providers, imposing a different type of interaction, and making him/her qualitatively more exposed and vulnerable to the transfer of traumatic content than the encounter with a person who experienced the same trauma several months or maybe years before. This result; however, could come as a surprise in light of the previous studies which showed traumatic events refugees and asylum seekers experience in their countries of origin to be more highly correlated to PTSD symptomatology, depression, and anxiety-related difficulties then traumatic events in the transit countries [ 42 , 54 ]. An explanation for these inconsistencies can potentially be found in the extent to which helping professionals can more easily link themselves or feel more responsible for traumatic events refugees experience in their own or the neighboring countries compared to the countries of origin, causing exposure to this content to have a greater impact on STS.…”
Section: Discussionmentioning
confidence: 86%
“…Secondary exposure to traumatic experiences was assessed using the Harvard Trauma Questionnaire, Part I (HTQ) [ 53 ], a cross-culturally validated and widely used check-list for measuring torture and trauma. For the purposes of this research, HTQ Part I, consisting of 64 traumatic experiences refugees could be faced with in their countries of origin [ 42 , 53 ] was adapted for use with service providers, together with the Stressful Experiences in Transit Questionnaire–Short Form (SET-SF) which includes a list of 19 traumatic experiences refugees could be exposed to during their transit [ 54 ]. Namely, with both check-lists, participants were asked to indicate which of the traumatic experiences from the comprehensive lists was shared with them during their work by a person who directly experienced it.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation